The bacterial signal indole increases epithelial-cell tight-junction resistance and attenuates indicators of inflammation - Bansal, Tarun (National Academy of Sciences, 2009)
Interkingdom signaling is established in the gastrointestinal tract in that human hormones trigger responses in bacteria; here, we show that the corollary is true, that a specific bacterial signal, indole, is recognized as a beneficial signal in intestinal epithelial cells. Our prior work has shown that indole, secreted by commensal Escherichia coli and detected in human feces, reduces pathogenic E. coli chemotaxis, motility, and attachment to epithelial cells. However, the effect of indole on intestinal epithelial cells is not known. Because intestinal epithelial cells are likely to be exposed continuously to indole, we hypothesized that indole may be beneficial for these cells, and investigated changes in gene expression with the human enterocyte cell line HCT-8 upon exposure to indole. Exposure to physiologically relevant amounts of indole increased expression of genes involved in strengthening the mucosal barrier and mucin production, which were consistent with an increase in the transepithelial resistance of HCT-8 cells. Indole also decreased TNF-α-mediated activation of NF-κB, expression of the proinflammatory chemokine IL-8, and the attachment of pathogenic E. coli to HCT-8 cells, as well as increased expression of the antiinflammatory cytokine IL-10. The changes in transepithelial resistance and NF-κB activation were specific to indole: other indole-like molecules did not elicit a similar response. Our results are similar to those observed with probiotic strains and suggest that indole could be important in the intestinal epithelial cells response to gastrointestinal tract pathogens.